Strategi Komunikasi Orangtua Siswa SD dalam Mendampingi Anak Belajar Masa Pandemi (Studi Kasus Orangtua Siswa SD Annur dan Mts Arahman Depok) - Santa Lorita Simamora; Dicky Andika; Yuliati (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The purpose of this study was to determine the reality of the communication strategies used by parents in accompanying their children of elementary school age during the pandemic, specifically in the Pondok Cina area, Depok, West Java. The research informants numbered around 5 mothers as parents of elementary school students who live in Pondok Cina from social economic status C (simple) who help their husbands to earn a living.This study uses a constructivist paradigm that sees reality not by itself, but through interactions between one individual and another. To see more deeply how the description of the reality of the communication strategies used by parents in accompanying their children of elementary school age during a pandemic through a case study method that can explore how in a pandemic condition mothers as the closest parents use communication strategies in accompanying their son or daughter to learn online way.Research informants were taken using a purposive sampling technique (as needed), specifically the snowball technique. The case study method is a way to examine research cases and collect data through non-participant observation, and the largest portion is through in-depth interviews with research informants while maintaining health procedures set by the government. Furthermore, the author also elaborates through documentation studies of various documents related to the research theme.The results of data collection will be analyzed with the Huberman and Miles data analysis model with predetermined stages starting from reducing data, categorizing to drawing conclusions, finally the categories of communication strategies used by mothers in accompanying children during online learning via the internet are found.